DAMPAK KLAUSULA KONTRAK LISENSI PATEN TERHADAP PROGRAM ALIH TEKNOLOGI DI INDONESIA - Bakti Trisnawati (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2010)
There are positive and negative impacts in the contract clauses of patent license toward the program of transfer of technology in Indonesia. The positive one is the clause of Grand Back and Research and Development. Both clauses are balanced, not inflicting a loss upon one of the parties. Whereas the negative one is the clause of Tie In (tie-in clause). In this clause there is a tendency in the license owner from abroad to limit the development of technology owned by technology tenant, that is, Indonesia by including the clauses of limitation in the license contract.